2004
DOI: 10.1159/000078462
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Pimecrolimus Cream 1% in Adults with Moderate Atopic Dermatitis

Abstract: Background: Pimecrolimus cream 1% is a non-steroid, selective inflammatory cytokine inhibitor indicated for atopic dermatitis (AD). Objective: To compare the safety and efficacy of pimecrolimus cream 1%-based treatment versus conventional therapy in adults with moderate AD. Methods: Patients were randomized to receive pimecrolimus cream 1% (n = 62) or vehicle (n = 68) at the first signs/symptoms of AD, for 24 weeks as required. A moderately potent topical corticosteroid (prednicarbate 0.25% cream) was allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 13 publications
8
80
2
3
Order By: Relevance
“…Short- and long-term trials including pediatric and adult patients with AD have demonstrated the effectiveness of pimecrolimus [35,36,37,38,39,40,41,42,43,44]. …”
Section: Topical Treatments For Admentioning
confidence: 99%
“…Short- and long-term trials including pediatric and adult patients with AD have demonstrated the effectiveness of pimecrolimus [35,36,37,38,39,40,41,42,43,44]. …”
Section: Topical Treatments For Admentioning
confidence: 99%
“…[2][3][4][5] This shift in focus has highlighted methodological issues regarding the definition of a flare, for which there is currently no clear guidance or agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The CASM-DE-01 Study Group defined relapse in their 2 articles as a period of at least 3 consecutive days in which moderately potent topical corticosteroid application was considered necessary (a named corticosteroid was selected for use in each participating country). 3,15 In this group's second article in 2004, they specified that the corticosteroids must be considered necessary by the investigator in their definition of flare, 3 a point that was not clear in the 2002 article. 15 Zaki et al 16 stated that the need to use potent topical corticosteroids or further systemic treatment constituted a relapse.…”
Section: Behavioral Definitionmentioning
confidence: 99%
“…During the development program, several double-blind (DB) and open-label (OL) clinical studies were conducted in adult and paediatric patients treated intermittently with pimecrolimus cream 1% for up to 2 years [22, 23, 31,38,39,40,41,42,43]. No clinically relevant systemic side effects and no clinically significant treatment-related laboratory abnormalities were observed in these studies.…”
Section: Adverse Events In Clinical Trialsmentioning
confidence: 99%